1984
DOI: 10.1084/jem.160.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guérin-activated murine macrophages kill syngeneic melanoma cells under strict anaerobic conditions.

Abstract: We have studied the spontaneous killing of B5(59) melanoma cells by Bacillus Calmette-Guérin (BCG)-elicited macrophages under strictly anaerobic conditions to investigate the role of oxygen in macrophage-mediated cytotoxicity. The number of melanoma cells capable of forming colonies after aerobic or anaerobic incubation with BCG-macrophages was used as the index of cytotoxicity. The BCG-macrophages killed melanoma cells regardless of the amount of oxygen present. The killing observed was proportional to the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A macrophage cell line, IC-21, produced identical antilarval effects when stimulated with an LK (20) despite its inability to demonstrate a respiratory burst associated with H202 or O2 production (28), indicating that such reactive oxygen species are not required for larval killing. Similar results have been reported for macrophage tumoricidal activity (9,28).…”
supporting
confidence: 90%
“…A macrophage cell line, IC-21, produced identical antilarval effects when stimulated with an LK (20) despite its inability to demonstrate a respiratory burst associated with H202 or O2 production (28), indicating that such reactive oxygen species are not required for larval killing. Similar results have been reported for macrophage tumoricidal activity (9,28).…”
supporting
confidence: 90%
“…The resulting solution containing cells and dissolved gel components was diluted 10–1,000-fold (depending on the initial B16 cell concentration in the gel) in OT-1 growth medium and 100-µl aliquots of the final dilution were plated in each of two 60 × 15-mm tissue culture dishes containing 2 ml OT-1 growth medium. The dishes were incubated at 37°C for 7 d in a 95% air/5% CO 2 humidified atmosphere to allow B16 cells to form macroscopic colonies, washed with PBS, treated with 2 ml of 3.7% formaldehyde in PBS for 15 min to fix the B16 cells, washed again with PBS, incubated for 2 h in 2 ml of 4% wt/vol methylene blue in H 2 O at room temperature, washed with distilled water to remove excess methylene blue, dried, and the blue-stained colonies counted manually as previously described ( Freedman et al, 1984 ). Control experiments showed that B16 cells had a plating efficiency of ∼60% regardless of whether they were released from plastic tissue culture plates with EDTA or from collagen-fibrin gels with collagenase and trypsin and/or plated in β-ME–containing medium.…”
Section: Methodsmentioning
confidence: 99%
“…We selected activated CD8 + OT-1 cells as effector cells and SIINFEKL peptide–pulsed B16 melanoma cells as target cells for these studies because both cell types and their interactions had been well characterized in vitro ( Moore et al, 1988 ; Ochalek et al, 1988 ; Snyder et al, 2003 ; Regoes et al, 2007 ) and in vivo ( Dobrzanski et al, 2001 ; Regoes et al, 2007 ). To quantitatively assess OT-1 cell–mediated cytolysis of SIINFEKL peptide–pulsed B16 cells, we used a newly designed three-dimensional collagen-I–fibrin gel system and a previously described clonogenic assay for B16 mouse melanoma cells ( Freedman et al, 1984 ). We report in this paper that in every situation examined (i.e., individual SIINFEKL-B16 cells and SIINFEKL-B16 cells in spheroids [ Sutherland, 1988 ] in collagen-fibrin gels and SIINFEKL-B16 cells in centrifugally packed cell pellets), OT-1 T cell–mediated killing of SIINFEKL-B16 cells was strictly dependent on OT-1 cell concentration.…”
mentioning
confidence: 99%
“…bacillus Calmette-Guerin (BCG) alone and in combination with chemotherapy and other immunotherapies has been used to treat melanoma [5][6][7][8]. This bacterial therapy provides immunostimulatory DNA and activates the TLR9-MyD88 pathway [9], which leads to activation of macrophages and dendritic cells (DCs) and the production of various cytokines [9,10]. These activated innate immune cells can also prime tumor-specific T cells against various TAAs and generate anti-tumor immunity.…”
Section: It Immunotherapy With Bacteriamentioning
confidence: 99%